Cluster of acute poisonings associated with an emerging ketamine analogue, 2-oxo-PCE. (September 2018) - Tang, Magdalene H.Y.; Chong, Y.K.; Chan, Candace Y.; Ching, C.K.; Lai, C.K.; Li, Y.K.; Mak, Tony W.L.
Highlights: An emerging ketamine analogue, 2-oxo-PCE, was identified in a recent outbreak. 2-oxo-PCE had ketamine-like adverse effects but was potentially more toxic. There is a higher incidence of impaired consciousness, convulsion and hypertension. Routine toxicology screening methods may not detect 2-oxo-PCE. Abstract: Ketamine and phencyclidine are well-known drugs of abuse of the arylcyclohexylamine class, the backbone of which is used for the synthesis of new psychoactive substances (NPS). In October 2017, a cluster of acute intoxications was encountered where patients presented with ketamine-like toxidrome. Upon initial toxicology screening, however, neither ketamine nor other causative agents were detected in the patients' urine. Instead, an unidentified substance was consistently detected. Further investigations using gas- and liquid-chromatography mass spectrometry led to the identification of an arylcyclohexylamine analogue, 2-oxo-PCE. The present study reports the analytical and toxicological profile of this emerging NPS. Chart review found, in total, 56 cases of 2-oxo-PCE associated acute poisoning between October and November 2017. Laboratory analysis confirmed the presence of 2-oxo-PCE in the urine of all patients; nasal swab samples from three patients revealed the lone presence of 2-oxo-PCE. Urine bedside immunoassay for ketamine was found not to cross-react with 2-oxo-PCE. In 55% of the cases, other drugs of abuse were detected on toxicology analysis; whilst in the remainder, 2-oxo-PCE was used alone. The main clinical symptoms associated with sole 2-oxo-PCE use include impaired consciousness (84%), confusion (60%), abnormal behaviour (44%), hypertension (80%) and tachycardia (40%). Convulsion (16%) was also observed relatively frequently. Management was mainly supportive, whilst three patients required intensive care. All patients recovered uneventfully. In conclusion, frontline clinical and laboratory personnel should be highly vigilant in the lookout for 2-oxo-PCE, a dangerous emerging arylcyclohexylamine analogue.